Concepções e práticas pedagógicas acerca da construção do número voltados para a educação de alunos com deficiência visual - Silva, Ana Mara Coelho da (Universidade Federal do Pará, 2020)
This study aimed to investigate the conceptions and pedagogical practices concerning the construction of the notion of number implemented by teaches of the Pedagogical Intervention sector of a polo institution, which serves students with visual impairment. To support the investigation of this problem, we support the notes of Piaget epistemological approach. The research is part of the qualitative research, in the action research modality, developed with seven participants, including two teachers directly involved in the work of the Pedagogical Intervention sector, and five students with visual impairment, attending this learning environment. The research consisted of an observation phase of the activities developed within the teaching of mathematics and specifically related to the object of this research, the numbers, with a duration of three months; semi-structured interviews directed to the teachers and legal guardians of the students selected for this study, in order to understand how mathematical teaching and learning relationships were implemented and maintained within the Specialized Educational Unit (UEES) and in the regular educational context. Then, problem situations were selected and elaborated, which Piaget and Szeminska (1975) propose as primordial for the student to construct the notion of number. The results showed that the lack of teacher training has contributed to mistaken educational practices based on empiricism, without the proper foundation of a theoretical approach. In addition to a teaching centered on memorization and repetition, in which the student learns when exercising certain skills, such as counting numbers, with little daily applicability and that does not allow the student to feel part of the learning process. Likewise, we realize that there is a fragmentation, discontinuity and decontextualization of the work carried out between the various sectors of (UEES) and of these with regular education. Through the activities implemented with the students, it was possible to realize that there is a need for a pedagogical action, with didactic-pedagogical planning, which enables the student to develop mathematical logical reasoning actively.